Preference, Outcome and Cost of Caesarean Sections: Comparison Between Public and Private Tertiary Hospitals - Sabnam, Nazia; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2021)
Background: To compare preference, outcome and cost of caesarean sections between public and private tertiary hospitals. Methods: This comparative cross sectional study was conducted among 152 conveniently selected women who underwent CS. Data were collected by face to face interview and record reviewing by using semi-structured questionnaire and check list, ethical issues were maintained. Total cost was estimated by direct and indirect cost related to CS, analysis done by SPSS software. The study was conducted in Obstetrics and Gynaecology department of Dhaka Medical College & Hospital and Holy Family Red Crescent Medical College Hospital from January to December, 2018. Results: Mean monthly family income of women was Tk.19668.75 (±14115.02) in public and Tk. 55472.22 (±25044.17) in private hospital. Provider preference was higher in public (78.8%) while self-preference was higher in private (37.5%) hospital (p<0.05). Majority i.e. 70% and 72.2% of women in public and private hospital respectively were healthy. But majority i.e. 58.3% had complications of new born in private compared to public (31.3%) hospital (p<0.05). In private hospital, mean total cost (Tk.52776.07±15841.93), direct cost (Tk.50826±15321.92) and indirect cost (Tk. 2890.91±3752.38) of CS was significantly higher compared to mean total cost (Tk.10149.2±4298.46), direct cost (Tk.8320.45±4028.74) and indirect cost (Tk.1844.87±1154.80) in public hospital (t-test, p<0.01). By selfpreference, majority i.e. 17(63%) of women had highest cost (Tk. >5000) in private hospital (p<0.05) while majority i.e. 10 (58.8%) of women had lowest cost (Tk.4000-10000) in public hospital. Conclusion: In private hospital total cost was about five times higher compared to public hospital though maternal outcome was almost same and neonatal outcome was better in public hospital. Appropriate regulations need to reduce preference of CS and difference of total cost. JOPSOM 2020; 39(2): 59-69